The effect of different teaching models on improving nursing humanistic care competencies: a network meta-analysis - Xiao Meixia; Xiong Qin; Jiang Rong; Li Lingxia; Fu Wenhao (Frontiers in Genetics)
ObjectivesTo evaluate the effectiveness of 13 teaching modes in improving nurses’ humanistic care ability using a Bayesian network meta-analysis.MethodsA computer-based search was conducted in PubMed, Web of Science, Cochrane Library, Embase, CBM, CNKI, WanFang, and VIP databases from their inception until 20 December 2024. Two researchers independently screened the literature, extracted data, and assessed the included studies using the bias risk assessment tool recommended by the Cochrane Handbook for Systematic Reviews of Interventions 5.1.0. The heterogeneity test was performed using RevMan 5.3 software, while the network meta-analysis and publication bias test were conducted using Stata 15.0 software.ResultsA total of 21 studies involving 13 teaching modes (12 innovative teaching modes and Traditional Teaching Mode) and a combined sample size of 878 participants were included. All included studies were rated as either A or B in quality evaluation. Compared with the traditional teaching mode, the other 12 innovative teaching modes were more effective in enhancing nurses’ humanistic care ability, with statistically significant differences (P < 0.05). Among the 12 innovative teaching modes included, the “Peer Sister Teaching Mode” had superior teaching effectiveness compared to the other teaching modes. The Lasswell Teaching Mode was more effective than the Carolina Teaching Mode, Micro-video Teaching Mode, and Balint Teaching Mode. Additionally, the ADDIE Teaching Mode was more effective than the Carolina Teaching Mode and Micro-video Teaching Mode (P < 0.05). The cumulative ranking probability plot indicated that the “Learning from Sisters” teaching mode was the best for improving nurses’ humanistic care ability, with a probability of 91.7%.ConclusionThe “Peer Teaching Mode”, based on its peer - assisted and collaborative - learning approach, shows the most advantages in the network meta - analysis results. It is recommended that nursing management choose the “Peer Teaching Mode” as the best training strategy to enhance nurses’ humanistic care ability.